The Role of Business Ethics in Enhancing Reputation and Public Trust - Sania Andihta Br.Nainggolan (Patua : Journal of Business Administration and Management, 2024)
This study aims to analyze the role of business ethics in enhancing corporate reputation and public trust. In the era of globalization and information transparency, the implementation of business ethics is an important factor influencing public perception of a company. This study uses a quantitative approach with an associative design. Data were collected through questionnaires from 120 respondents selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression to examine the effect of business ethics on corporate reputation and public trust. The results show that business ethics has a positive and significant effect on corporate reputation with a coefficient of 0.65 and on public trust with a coefficient of 0.72. Simultaneous tests also show that business ethics simultaneously have a significant effect on both dependent variables. The coefficient of determination indicates that business ethics can explain 58% of the variation in corporate reputation and 64% of the variation in public trust. These findings indicate that implementing ethical values ​​such as honesty, transparency, and social responsibility can improve a company's image and build public trust. Therefore, companies are advised to integrate business ethics into their organizational culture to support long-term business sustainability.